INVALIDITY OF CONTRACT UNDER THE ITALIAN LAW - Anna A Novitskaya (RUDN Journal of Law, 2017)
The problems of regulating the invalidity of contract under the Italian law is dictated by the crisis of the pandect system of the division of irregular contracts into nullity and annullability. In particular, in the Italian doctrine and case-law attempted to add within the pandect system of invalidity of bargains supplement it with new types of irregular contracts, borrowed from the French civil law tradition. The author using comparative method and examines the invalidity of contract under the Italian law. Firstly, the Article deals with the influence of German and French legal regulation of invalidity of contracts on Italian Law. Secondly, the author discusses the difference between nullity (nullità) and annullability (an-nullabilità) of contracts and analyzes the basic concepts of contract law such as causa as the essential term of contract, for the most part, determines the organization of norms on the nullity of the treaty in Italian civil law. Also the Article focus on the public order, imperative norms under Italian contract law. In conclusion of the Article presents general conclusions on the regulation of nullity and annulla-bility under Italian contract law, as well as an overview of convalidation and conversion. The article is oriented to civilists interested in the comparative legal research and the Italian contract law.